Patient Preferences for Diabetes Treatment Among People With Type 2 Diabetes Mellitus in China: A Discrete Choice Experiment - Huang, Yuankai; Huang, Qixiang; Xu, Ailin; Lu, Mengqing; Xi, Xiaoyu (Frontiers in Public Health, 2022)
Introduction: The preferences for diabetes treatment related attributes may be significant in diabetes management. However, there is lack of evidence on diabetes patient preferences in China. Methods: A large-scale questionnaire survey was conducted in hospitals in mainland China. Participants’ preferences for six attributes were evaluated via a discrete choice experiment using the conditional logit model. The patients’ willingness to pay for each attribute was calculated based on the attribute of cost. Results: The sample consisted of 709 patients (male 51.9%; female 48.1%). The results of the model indicated that the patients’ preference weight of days that blood glucose level is under control per week was the highest (1.41), and the preference weight of blood glucose monitoring frequency was the lowest (0.642). The patients were generally willing to pay for improvements in their type 2 diabetes mellitus treatments, and patients had relatively higher willingness to pay to avoid blood glucose level within normal range 1 day/week (¥176.01) and avoid frequency of hypoglycemic events within 1-2/month (¥144.53). Conclusions: The days that blood glucose level is under control per week is the most important attribute in treatment choice for patients with type 2 diabetes mellitus in China, followed by frequency of hypoglycemic events, medication regimen, weight change and blood glucose monitoring frequency.